Effect of phospholipase A2 inhibitors during infection caused by Leishmania (Leishmania) amazonensis - Bordon, Maria L.A.C. [UNESP]; Laurenti, Márcia D.; Ribeiro, Susan Pereira; Toyama, Marcos H. [UNESP]; Toyama, Daniela de O.; Passero, Luiz Felipe D. [UNESP] (Springer Nature, 2018)
Background: Lipid metabolites play an important role in parasite differentiation and virulence. Studies have revealed that Leishmania sp. uses prostaglandins to evade innate barriers, thus enabling the parasites to survive inside immune cells. Despite the role of the enzyme Phospholipase A2 (PLA2) in prostaglandins production, few studies have investigated the role of parasite PLA2 during the interaction between L. (L.) amazonensis and the host (in vitro and in vivo) immune cells. Methods: In the present work, the leishmanicidal effect of PLA2 inhibitors, methyl arachidonyl fluorophosphonate (MAFP), bromoenol lactone (BEL) and aristolochic acid (AA) were investigated in vitro (promastigote and intracellular amastigote forms of L. (L.) amazonensis) and during in vivo infection using BALB/c mice. Results: The aforementioned inhibitors were deleterious to promastigote and amastigote forms of the L. (L.) amazonensis and were non-toxic to peritoneal macrophages from BALB/c mice. L. (L.) amazonensis-infected BALB/c mice treated with the inhibitor BEL presented decreased lesion size and skin parasitism; however, BEL treatment induced hepatotoxicity in BALB/c mice. Conclusions: Results presented herein suggested that PLA2 inhibitors altered L. (L.) amazonensis viability. In spite of liver toxicity, treatment with BEL was the most selective compound in vitro, as well in vivo, resulting in lower skin parasitism in the infected mice. These findings corroborate the role of PLA2 in parasite virulence and maintenance in vertebrate hosts, and suggest that molecules structurally related to BEL should be considered when planning compounds against Leishmania sp.
Keywords: BALB/c mice; Leishmania (Leishmania) amazonensis; Macrophages; Phospholipase A2; Phospholipase A2 inhibitors